OPTIMALISASI KOMPETENSI ANALIS SDM APARATUR MELALUI MENULIS ILMIAH - Marianus Keo (Badan Kepegawaian Negara | The National Civil Service Agency, 2021)
The study aims at analizing the correlation between the government’s policy regading the obligation to make academic writing, with the level of professionalism of civil servant as a whole and Human Resource Analist in special. Writing is an intellectual activity to create ideas in written form in order to communicate to the reader in regards with the aims of the message. Writing, like a life itself, is a voyage of discovery. The more they write, the more they find. Writing turns out to save a lot of wealth that can be reached by those who do it. This study found that writing has the benefit of being able to build the quality of everyone who takes part in it, including communication skills, self-actualization, increasing the ability to control oneself and the environment and improving critical thinking. These abilities will in turn improve the competence and professionalism of a Human Resource Analyst if it is done continuously. However, this proficient ability in writing will not come by itself without going through the several of education and training carried out by supervisory agencies, user agencies and professional organizations.